School-Based Management Approach in Improving Academic Performance: A systematic Review - Nurhayati, Lia (Newinera Publisher, 2025)
School based management (SBM) and the academic outcomes of the students are subjects of theories but not evenly supported, on the bases of evidences, in the context of education. This systematic review summarizes results of ten high-quality studies published in 20132024 and consider in detail how SBM affects academic outcomes and when its positive effects can be achieved. The review ascertains that SBM has the ability to boost academic performance especially when underpinned by effective leadership, interscholastic types of school cultures and good based management practices. Further examination has, however, thwarted by the existence of formidable contextual contingencies; the success of SBM, based on leadership ethics, community participation, structural equity and political support. Additionally, the existing evidence base has several major limitations, such as the lack of longitudinal research, the underemphasis on the aspect of equity, and bias towards the middle-income and urban environments. Unless specific protection mechanisms and capacity-building are put in place, space is created to expand the established inequalities instead of realizing the promised democratizing effects of SBM. The results encourage a new generation of SBM research that will seek to be more critical about the questions of power, equity and justice without being too narrowly balled as a strictly technocratic procedure with the aim of enhancing more inclusive and transformational modes of school governance.